The secret sheriff of sixth grade - Sonnenblick, Jordan (New York : Scholastic Press, 2017)
Maverick Falconer is just starting middle school and he wishes he were a hero like his father because maybe then he could deal with his mother's drinking and series of abusive boyfriends, not to mention the kids who bully him in middle school (pretty much the same ones who bullied him in elementary school)--but as the year passes he begins to realize that other kids have problems too, and maybe if they can all survive sixth-grade things will get better.
Keywords: Mothers and sons -- Juvenile fiction; Children of alcoholics -- Juvenile fiction; Dysfunctional families -- Juvenile fiction; Middle schools -- Juvenile fiction; Bullying -- Juvenile fiction; Friendship -- Juvenile fiction; Mothers and sons -- Fiction; Alcoholism -- Fiction; Family problems -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Bullying -- Fiction; Friendship -- Fiction